Developmental effects of stimulus gender and the social context in which it appears on threat detection. (19th December 2017) - Horovitz, Omer; Lindenfeld, Irit; Melamed, Maya; Shechner, Tomer
Abstract : This study used a hands‐free eye‐tracking visual search (VS) task to examine possible developmental differences in target detection. Thirty‐two young adults and 27 youth were asked to detect a fearful face (male or female) among a crowd of either neutral or happy faces. Fearful male faces were detected faster than fearful female faces, but only by young adults and only when displayed among neutral faces. Additionally, young adults had shorter scanpath lengths prior to the target detection. Finally, a strong negative correlation emerged between age and detection speed for a male target in a neutral crowd. Using this age‐matched VS task, the study found age differences in the way individuals detect a threat in a social‐related contextual environment, pointing to subtle differences in the emotion–attention interplay during the course of development. Statement of contribution What is already known on this subject? Visual search of threat detection is critical for survival, specifically regarding expressive faces. Visual search efficiency is affected by both stimulus‐driven and higher goal‐directed processes. Stimuli and contextual features affect threat speed detection. What does this study add? A novel task was designed to examine age‐related differences in visual search. Specific stimuli gender and contextual features yielded age‐related differences in threat detection. The study further demonstrates the subtle developmental differences in attention–emotion interaction.